ANOMALI DALAM KHAZANAH ARSIP: AFDEELING ATJEH ZAKEN DALAM ALGEMENE SECRETARIE (1873-1904): Array - Dharwis Widya Utama Yacob (Jurnal Kearsipan, 2010)
Algemene Secretarie was the government institution established in 1819. Algemene Secretarie assigned to advise and inform the Governor-General, to assess any proposal submitted by the head of department, edit all forms of decision (besluit), to edit the government newspaper, to take care of variety reports included statistical data that was sent by gewestelijke stukken and made by Dutch Government and reported to the Central Government in the Netherlands and also to coordinate the information among institutions in the Netherlands-Indie. In addition, the most important thing that Algemene Secretarie obtained duties was to keep archives. Algemene Secretarie kept the VOC archives period (Vereenigde Oost-IndischeCompagnie) and British rule period which was also called Engelsche Tussenbestuur. It was their duties to save all files of Algemene Secretarie that made them to create accessible archival systems in the Netherlands-Indie. Algemene Secretarie collections are the backbone of the Netherlands-Indie archives. They contained all activities, decisions and policies made by the Governor-General. The archives were the Netherlands-Indie recorded, arranged, and kept by the Algemene Secretarie. Similarly, they had a duty to correspondent with other departments such as Burgelijke Openbare Werken (BOW/Public Works Department during the Netherlands-Indie), Mijnwezen (Department of Mines during the Netherlands-Indie). From year to year, Algemene Secretarie had been growing so rapidly. Many new bureaus and sections conducting various tasks were developed, such as the Bureau of Indigenous Affairs (Bureau voor de Inlandsche Zaken), Section of Statistics (Afdeling Statistiek), and the Bureau of Preaching (Press Bureau). The more organization units grew the more function of keeping archives arose. This made Algemene Secretarie had a duty which was similar with instoragearchives. The interesting facts which were found was that Aceh collections were kept separatedly with other regions such as Sumatra, Java en Madoera, Borneo, and Groote Oost. Obviously, this indicated special meaning at that time. The partitioning was related to the retrieval process the Aceh archives. The proceedings, however, showed us that the policy of the Netherlands-Indie at that time was focused on what happened in Aceh. It can be seen from the Algemene Secretarie collections which big parts of the collections had called Afdeling Atjeh Zaken.